اثر التكوين قبل الخدمة في تنمية مهارات التدريس لدى اساتذة التعليم الابتدائي - عمار زهرة (كلية العلوم الاجتماعية, 2020)
Abstract : The aim of the current study was to know the effect of the formation pre – serving on teaching skills progressing specially primary school teachers. were the researcher used the description method and the analytical study. According to the previous point, was designed for measuring the effect of these type of formation on teaching skills development, by wich I wanna enter the field and get more closer from the reality of teaching. Also we focused in our study on ( behnass study 2019), (belmahdi study 2018), (shalali study 2009) to discussion of hypotheses , those deal the same topic were different in gethering the data of topic and varied in the result but it combined that the effect of formation pre-serving on teaching skills development was not what the goals were selected for those expectation .
Keywords: التكوين؛تكوين المعلمين؛المهارات التدريسية؛التعليم الابتدائي